Facial injury patterns associated with stand-up electric scooters in unhelmeted riders - Kim, Hyeon Seok; Kim, Woo Seob; Kim, Han Koo; Kang, Shin Hyuk; Bae, Tae Hui (Archives of Plastic Surgery, 2022)
Background In recent years, the number of people riding stand-up electric scooters in South Korea has increased rapidly. This study analyzed the facial injury patterns associated with stand-up electric scooter-related trauma in patients who visited our emergency center.Methods In this retrospective review, we collected data from patients who had visited our emergency center for stand-up electric scooter-related trauma between January 1, 2018 and December 31, 2020.Results The average age of the patients was 26.7 years. Of the 73 patients, 47 were male and 26 were female, highlighting a male predominance. Seven patients were injured after alcohol consumption. None of the patients had worn helmets. Additionally, upon comparing the frequency of facial injuries according to the quarter of the year, the facial injury rate was higher in the second and third quarters than in the first and fourth quarters. Facial soft tissue injuries were classified into facial cosmetic subunits and analyzed according to their location. The highest number of injuries was on the chin (n=18, 20.9%). Of the 73 patients with stand-up electric scooter-related facial injuries, 16 had acute facial osseous fractures. The commonest acute facial osseous fractures were those of the orbit (n=7, 26.9%).Conclusions The patterns of facial trauma reported here can be helpful for quickly evaluating and treating patients with facial trauma related to stand-up electric scooters. Additionally, people riding stand-up electric scooters should be aware of the risks associated with facial trauma and the importance of wearing protective devices, such as helmets and masks.
Keywords: Facial injuries; Electric; Scooter; Trauma